Crystal structure of (2,2′-bipyridyl)bis(4-bromobenzyl)dibromidotin(IV), C24H20Br4N2Sn - Lee See Mun; Lo Kong Mun; Tiekink Edward R.T. (Zeitschrift für Kristallographie - New Crystal Structures, 2019)
C24H20Br4N2Sn, monoclinic, P21/n (no. 14), a = 9.3186(1) Å, b = 16.2615(1) Å, c = 16.8482(1) Å, β = 100.748(1)°, V = 2508.29(4) Å3, Z = 4, Rgt(F) = 0.0254, wRref(F2) = 0.0688, T = 100(2) K.